Kerajaan dan Kesultanan Dunia Melayu: Kasus Sumatra dan Semenanjung Malaysia - Suwardi Mohammad Samin (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2015)
Study canopy above is the result of the investigation and writing in 2012 and passed in 2013 that the results have been a dummy book